Untersuchung des Sinterverhaltens von SrTiO? unter Berücksichtigung der Defektchemie - Lemke, Fabian (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
Space charge contributions to the densification of perovskite ceramics during sintering were assessed in the model system strontium titanate using a combined experimental and analytical approach. Defect chemistry in the bulk and at the grain-boundaries for SrTiO? in high temperature regions were calculated based on literature data. Diffusion coefficients for bulk-diffusion and grain boundary-diffusion were estimated and used with Coble's equations for densification rates.